A multilayer electro-thermal model of pouch battery during normal discharge and internal short circuit process. (25th June 2017) - Chen, Mingbiao; Bai, Fanfei; Song, Wenji; Lv, Jie; Lin, Shili; Feng, Ziping; Li, Yongliang; Ding, Yulong
Highlights: 2D network equivalent circuit considers the interplay of cell units. The temperature non-uniformity Φ of multilayer model is bigger than that of lumped model. The temperature non-uniformity is quantified and the reason of non-uniformity is analyzed. Increasing the thermal conductivity of the separator can effectively relieve the heat spot effect of ISC. Abstract: As the electrical and thermal characteristic will affect the batteries' safety, performance, calendar life and capacity fading, an electro-thermal coupled model for pouch battery LiFePO4 /C is developed in normal discharge and internal short circuit process. The battery is discretized into many cell elements which are united as a 2D network equivalent circuit. The electro-thermal model is solved with finite difference method. Non-uniformity of current distribution and temperature distribution is simulated and the result is validated with experiment data at various discharge rates. Comparison of the lumped model and the multilayer structure model shows that the temperature non-uniformity Φ of multilayer model is bigger than that of lumped model and shows more precise. The temperature non-uniformity is quantified and the reason of non-uniformity is analyzed. The electro-thermal model can also be used to guide the safety design of battery. The temperature of the ISC element near tabs is the highest because the equivalent resistance of the external circuit (not including the ISC element) is the smallest when the resistance of cell units is small. It is found that increasing the thermal conductivity of integrated layer can effectively relieve the heat spot effect of ISC.